2023
DOI: 10.1029/2023gl104541
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Cloud Dynamics and Microphysics During the Rapid Intensification of Super‐Typhoon Nanmadol (2022) Based on Multi‐Satellite Observations

Abstract: Using multi‐satellite observations, the cloud dynamic and microphysical characteristics were revealed during the rapid intensification (RI) of super‐typhoon Nanmadol (2022). As the storm intensifies, the eyewall contracts, the upper‐level divergence strengthens, and the cirrus cloud increases, leading to stronger upper‐level radial outflow and the vertical updraft. Meanwhile, it is found that there exists a dynamically attractive area in the outer rainbands, where particles grow effectively and form “a small a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…TC 30-60kt cases exhibit a significant positive correlation between CWPs in the inner-core and outer-core regions, while TC 60-90kt show a significant negative correlation, especially when the evolution of the hydrometeor in the outer-core region led to 3 h. This might be the different models of hydrometeor content increase in the inner-core region for the weak and strong TCs associated with those in the outer-core region. In a recent study on the super-Typhoon Nanmadol (2022), it is found that there is a small amount of large particle region approximately 300 km from the eye in the post-period of RI (Wu et al, 2023). This implies that the outer-core region of strong TCs is a particular area of hydrometeor evolution during the RI.…”
Section: Resultsmentioning
confidence: 99%
“…TC 30-60kt cases exhibit a significant positive correlation between CWPs in the inner-core and outer-core regions, while TC 60-90kt show a significant negative correlation, especially when the evolution of the hydrometeor in the outer-core region led to 3 h. This might be the different models of hydrometeor content increase in the inner-core region for the weak and strong TCs associated with those in the outer-core region. In a recent study on the super-Typhoon Nanmadol (2022), it is found that there is a small amount of large particle region approximately 300 km from the eye in the post-period of RI (Wu et al, 2023). This implies that the outer-core region of strong TCs is a particular area of hydrometeor evolution during the RI.…”
Section: Resultsmentioning
confidence: 99%
“…On 18 September (UTC), as shown in Figure 3d, Nanmadol developed two eye structures and began the process of eye-wall replacement prior to landfall. This phenomenon, where a strong typhoon replaces a smaller eye with a larger one, is part of its structural adjustment and represents a vulnerable phase during which the typhoon's intensity typically weakens [49]. Landfall occurred during the critical period of Nanmadol's eye-wall replacement, which was unsuccessful, leading to the typhoon striking Japan in this vulnerable state.…”
Section: Wave Simulation Resultsmentioning
confidence: 99%
“…They then investigated the impact of the satellite retrievals on assimilation and forecasts for Typhoon Chaba and Ma-on in 2022. Wu et al [49] revealed the cloud dynamic and microphysical characteristics during the rapid intensification (RI) of Super Typhoon Nanmadol in 2022 by using multi-satellite observations; among them, the high-resolution FY-4B satellite observed the structure of the typhoon eye clearly, allowing the structural characteristics of the typhoon eye wall to be identified.…”
Section: Introductionmentioning
confidence: 99%